Empowerment of Business Management at TPS3R Taruna Jaya, Desa Adat Tojan, Blahbatuh, Gianyar - Santini, Ni Made; Dewi, Made Pratiwi; Tamansari, Ni Made (Asian Journal of Community Services, 2024)
Gianyar, a prominent cultural tourism destination in Bali, has evolved into a global tourist hotspot, prompting local modernization with waste management emerging as a critical issue. TPS3R Taruna Jaya in Desa Adat Tojan, Blahbatuh, Gianyar, exemplifies a solution through its waste management infrastructure, converting waste into compost to benefit environmental conservation. Universitas Warmadewa engages in enhancing the compost potential of TPS3R Taruna Jaya through initiatives in production management, marketing, and finance. This collaboration aims to augment production capacity, bolster marketing efforts, enhance human resources, and increase sales and company assets for the TPS3R Taruna Jaya group. Implementation involves mentoring and training in waste sorting, compost packaging, storage systems, label creation, promotional strategies, financial reporting, and equipment acquisition.